Hand Blockage Impact on 5G mmWave Beam Management Performance - Filipa Fernandes; Christian Rom; Johannes Harrebek; Simon Svendsen; Carles Navarro Manchon (IEEE Access, 2022)
Modelling and managing user-induced rotation and blockage in handheld multi-antenna panel devices are some of the pivotal challenges of future narrow beam millimeter wave (mmWave) communications. While studies have been conducted separately on multi-panel beam management (BM) performance and mmWave user blockage loss, no study has been made to date, to the best of the authors’ knowledge, on how hand blockage influences beam alignment accuracy in the context of 5G new radio (NR). This paper presents a link-level evaluation on the impact of user hand grip in BM performance under a 5G NR standard compliant signalling and measurement framework. A high-detail handset model is employed, equipped with multiple panels and different hand grips obtained with CST Microwave Studio, a 3D electromagnetic field simulation tool. Additionally, this study incorporates aspects such as intra-cell mobility, device rotation, hand grip variability and changing propagation conditions. Results show that hand blockage can significantly degrade beam alignment performance, particularly for dual-hand grips in predominantly line-of-sight (LOS) environments. Finally, results suggest that the current blockage model proposed by 3GPP must be further enhanced to account for blockage on a per-panel basis. This would allow a more accurate portrayal of user hand behaviour, which would support the analysis and design of effective solutions to overcome the user’s unpredictable shadowing effects at mmWave frequencies.